Method for preparing terephthalic acid through hydrogenation degradation of waste polyester plastics

The waste polyester plastic is directly hydrogenated into high-purity terephthalic acid through batch autoclave and transition metal carbide catalyst, which solves the problems of solvent use and multi-step processing in the prior art, and achieves high efficiency and low efficiency Cost polyester plastic recycling.

CN119191957APending Publication Date: 2024-12-27XIAMEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411324612.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the prior art, the chemical recycling process of waste polyester plastics requires a large amount of solvent, resulting in increased production costs, and the product purity and separation difficulty are high. The hydrogenation degradation product is PX and requires further processing to produce terephthalic acid.

Method used

The batch-type autoclave and transition metal carbide catalyst are used to hydrogenate and degrade waste polyester plastics into high-purity terephthalic acid under the action of the catalyst, avoiding solvent use and multi-step processing.

Benefits of technology

It realizes the direct degradation of waste polyester plastics to terephthalic acid with high efficiency and low cost, with excellent catalytic activity, high product yield, good catalyst stability and reduced production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191957A_ABST
    Figure CN119191957A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing terephthalic acid through hydrogenation degradation of waste polyester plastics, and relates to the field of hydrogenation degradation of waste plastics. A high-pressure reaction kettle is adopted, under the action of transition metal carbide, waste polyester plastics are heated and stirred in the H2 atmosphere, and terephthalic acid (PTA) is generated through solvent-free hydrogenation degradation. The transition metal carbide is at least one of molybdenum carbide, tungsten carbide, vanadium carbide, iron carbide and rhenium carbide; the polyester plastic is at least one of polyethylene terephthalate (PET) and polybutylene terephthalate (PBT). The reaction temperature ranges from 180 DEG C to 300 DEG C, the reaction hydrogen pressure ranges from 0.1 MPa to 8 MPa, and the reaction time ranges from 0.1 h to 24 h. The catalyst has the advantages of simple preparation method, good catalytic performance, good stability, high terephthalic acid yield, high purity and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of hydrogenation degradation of waste plastics, and in particular to a method for preparing terephthalic acid by hydrogenation degradation of waste polyester plastics. Background Art

[0002] Polyester plastics are widely used in the manufacture of fibers, sheets and films due to their high mechanical properties, good heat resistance, excellent dimensional stability and friction resistance. They are also widely used in food and beverage packaging, electronic and communication equipment, automotive parts, lighting products, sporting goods, health care, construction and other fields. The widespread use of polyester plastics has greatly facilitated modern human life, but due to their inherent stability and durability, they are difficult to degrade naturally. Waste plastics abandoned in nature not only bring serious environmental pollution, but also cause a waste of carbon resources. Therefore, the development of efficient methods for chemical recycling and high-value utilization of waste polyester plastics has received widespread attention.

[0003] At present, the chemical recycling of waste polyester plastics mainly uses solvent method to recover polyester plastic monomers. For example, polyester plastics are degraded into monomers, monomer esters or amines under high temperature and catalyst by hydrolysis, alcoholysis, aminolysis and other methods. The obtained products can be used as monomers again to produce polyester or polyamide after purification, so as to realize the recycling of resources. However, this process requires the consumption of a large amount of solvent, which increases the production cost, and the use of homogeneous catalysts in the reaction process causes the product separation purity to decrease. Compared with the solvent hydrolysis method, the conversion of polyester plastics into terephthalic acid monomers or aromatic compounds such as PX by hydrogenation degradation has the advantages of high reaction efficiency, high product yield and purity, and the reaction does not require the use of solvents, the products are easy to separate, and the operation is simple. For example, Chinese patent CN105712833A uses RuSnPt as a catalyst, and the reaction temperature is 240-350°C, the hydrogen partial pressure is 3-7MPa, and the reaction is 3-13h. The yield of PX is as high as 93%. Chinese patent CN116393139A constructs a catalyst with Cu as the active component, Zn, Mn, Sn, Ni, Co or Ca as the auxiliary agent, and Nb2O5, Al2O3, ZrO2, TiO2, MgO, CeO2 or SiO2 as the carrier. Under the conditions of reaction temperature of 180-300°C and hydrogen partial pressure of 0.2-8MPa, the reaction time is 0.5-20h, and the yield of PX can reach up to 98.2%. However, the hydrogenation degradation product of this method is PX, which needs to be further processed to obtain terephthalic acid in order to produce polyester plastics or polyester fibers such as polyethylene terephthalate (PET). Summary of the invention

[0004] The purpose of the present invention is to solve the above-mentioned problems in the prior art and to provide a method for preparing terephthalic acid by hydrogenation degradation of waste polyester plastics. The method can directly catalyze the hydrogenation degradation of waste polyester plastics to prepare high-purity terephthalic acid monomers instead of aromatic compounds such as PX, thereby realizing the recovery of polyester plastic monomers.

[0005] Taking the preparation of PTA monomer by hydrogenation degradation of PET in the present invention as an example, the chemical reaction equation is as follows:

[0006]

[0007] In order to achieve the above object, the present invention adopts the following technical scheme:

[0008] A method for preparing terephthalic acid by hydrogenation degradation of waste polyester plastics, using an intermittent high-pressure reactor, under the action of a catalyst transition metal carbide, catalytic hydrogenation degradation of waste polyester plastics into terephthalic acid. Wherein, the waste polyester plastics are at least one of polyethylene terephthalate (PET) and polybutylene terephthalate (PBT); the transition metal carbide is at least one of molybdenum carbide, tungsten carbide, vanadium carbide, iron carbide, and rhenium carbide.

[0009] The transition metal carbide is selected from hexagonal molybdenum carbide (β-Mo2C), cubic molybdenum carbide (α-MoC 1-x ), hexagonal tungsten carbide (α-WC), cubic tungsten carbide (β-WC), vanadium carbide (VC), iron carbide (FeC x ), rhenium carbide (ReC x ) at least one of.

[0010] The preparation of the transition metal carbide comprises the following steps:

[0011] Firstly, a soluble transition metal precursor and 2-methylimidazole are dissolved in deionized water, a hydrochloric acid solution with a concentration of 1 mol / L is added thereto, and then stirred at room temperature; a transition metal carbide is obtained through centrifugation, washing, drying and calcination.

[0012] The soluble transition metal precursors include: ammonium heptamolybdate tetrahydrate, sodium molybdate, ammonium tungstate, ammonium metatungstate, sodium tungstate, sodium metatungstate, ammonium vanadate, ammonium metavanadate, ammonium perrhenate, ferric chloride, ferric nitrate, ferric acetylacetonate, ferric sulfate, and ferric acetate.

[0013] The molar ratio of the soluble transition metal precursor to 2-methylimidazole is 1:1-10; the molar ratio of the soluble transition metal precursor to hydrochloric acid is 1:0.1-4;

[0014] The stirring time is 0.5 to 4 hours;

[0015] The drying temperature is 60-120°C, the drying atmosphere is one of vacuum / inert gas / air, and the drying time is 4-12 hours;

[0016] The calcination atmosphere is one of nitrogen, argon, 5% to 100% H2 hydrogen-argon or hydrogen-nitrogen mixed gas; the calcination temperature is 600 to 900° C., and the calcination time is 1 to 24 hours.

[0017] The method for preparing terephthalic acid by hydrogenation degradation of waste polyester plastics has the following specific steps of catalytic reaction: placing the catalyst and waste polyester plastics in an intermittent high-pressure reactor, charging H2 into the reactor at room temperature; then heating the intermittent high-pressure reactor to the reaction temperature and reacting for a period of time under stirring to degrade the polyester plastics into PTA monomers.

[0018] In the intermittent high-pressure reactor, the amount of catalyst used accounts for 1% to 20% of the total mass of waste polyester plastics; the pressure of H2 is 0.1 to 8 MPa, the reaction temperature is 180 to 300°C; the stirring rate is 0 to 300 rpm; and the reaction time is 0.1 to 24 hours.

[0019] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0020] 1. The method provided by the present invention directly degrades waste polyester plastics into terephthalic acid monomers instead of PX.

[0021] 2. The present invention shows excellent catalytic activity for preparing terephthalic acid by hydrogenation degradation of waste polyester plastics, high product yield and good catalyst stability. At a reaction temperature of 180-300°C, the conversion rate of waste polyester plastics reaches 100%, and the terephthalic acid yield is >90%. The catalyst used has good stability, and the reaction performance remains basically unchanged after 10 cycles.

[0022] 3. The transition metal carbide catalyst used in the present invention has excellent adsorption and activation capabilities for H2 and CO bonds in polyester plastics, and exhibits excellent catalytic performance.

[0023] 4. The transition metal carbide catalyst used in the present invention does not contain precious metal elements, the catalyst production cost is low, the preparation process is simple and controllable, and it can be mass-produced.

[0024] 5. Since the method of the present invention does not require the use of a large amount of solvent and the catalyst cost is relatively low, the overall production cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The following is the hydrogen nuclear magnetic spectrum of the terephthalic acid product obtained by the method of the present invention. DETAILED DESCRIPTION

[0026] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0027] Example 1: Dissolve 4.0g of ammonium heptamolybdate tetrahydrate and 1.3g of 2-methylimidazole in 40mL of deionized water, add 30mL of 1mol / L hydrochloric acid solution, and stir at room temperature for 0.5h. Centrifuge and wash twice with deionized water and ethanol respectively to obtain a solid product. Then dry it in a 60°C oven for 12h. The dried solid product is placed in a tubular furnace, introduced with Ar, and heated to 700°C at a rate of 3°C / min, maintained for 1h, and cooled to room temperature to obtain a molybdenum carbide catalyst. Take 0.1g of the prepared molybdenum carbide catalyst and 1.0g of polyethylene terephthalate (PET), place them in a high-pressure reactor, fill the reactor with 1.5MPa of hydrogen at room temperature, heat to 260°C, react for 4h, the conversion rate of PET reaches 100%, the selectivity of PTA in the solid product is higher than 99%, and the PTA yield is as high as 90%. See Figure 1 The following is the hydrogen nuclear magnetic spectrum of the terephthalic acid product obtained by the method of the present invention.

[0028] Example 2: 4.0g of ammonium heptamolybdate tetrahydrate and 1.3g of 2-methylimidazole were dissolved in 40mL of deionized water, and 30mL of hydrochloric acid solution with a concentration of 1mol / L was added, and stirred at room temperature for 0.5h. Centrifuge and wash twice with deionized water and ethanol respectively to obtain a solid product. Then dry it in a 60℃ oven for 12h. The dried solid product was placed in a tube furnace, passed through Ar, and heated to 700℃ at a rate of 3℃ / min, maintained for 1h, and cooled to room temperature to obtain a molybdenum carbide catalyst. Take 0.1g of the prepared molybdenum carbide catalyst and 1.0g of polybutylene terephthalate (PBT), place them in a high-pressure reactor, fill the reactor with 1.5MPa of hydrogen at room temperature, heat to 300℃, react for 6h, the conversion rate of PBT reaches 100%, the selectivity of PTA in the solid product is higher than 99%, and the PTA yield is as high as 92%.

[0029] Example 3: 4.0g of ammonium tetrahydrate heptamolybdate and 1.3g of 2-methylimidazole were dissolved in 40mL of deionized water, and 30mL of 1mol / L hydrochloric acid solution was added, and stirred at room temperature for 0.5h. Centrifuge and wash twice with deionized water and ethanol respectively to obtain a solid product. Then dry it in a 60℃ oven for 12h. The dried solid product was placed in a tube furnace, Ar was introduced, and the temperature was raised to 700℃ at a rate of 3℃ / min, maintained for 1h, and cooled to room temperature to obtain a molybdenum carbide catalyst. Take 0.1g of the prepared molybdenum carbide catalyst, 0.5g of polyethylene terephthalate (PET), and 0.5g of polybutylene terephthalate (PBT) and place them in a high-pressure reactor. At room temperature, 1.5MPa of hydrogen was filled into the reactor, heated to 300℃, and reacted for 4h. The conversion rate of PET reached 100%, the selectivity of PTA in the solid product was higher than 99%, and the PTA yield was as high as 91%.

[0030] Example 4: 4.0g of ammonium heptamolybdate tetrahydrate and 1.3g of 2-methylimidazole were dissolved in 40mL of deionized water, and 30mL of hydrochloric acid solution with a concentration of 1mol / L was added, and stirred at room temperature for 0.5h. Centrifuge and wash twice with deionized water and ethanol respectively to obtain a solid product. Then dry it in a 60℃ oven for 12h. The dried solid product was placed in a tube furnace, and a 5% H2 / Ar mixed gas was introduced. The temperature was raised to 700℃ at a rate of 3℃ / min, maintained for 6h, and cooled to room temperature to obtain a molybdenum carbide catalyst. Take 0.1g of the prepared molybdenum carbide catalyst and 1.0g of polyethylene terephthalate (PET), place them in a high-pressure reactor, fill the reactor with 1.5MPa of hydrogen at room temperature, heat to 280℃, react for 4h, the conversion rate of PET reaches 100%, the selectivity of PTA in the solid product is higher than 99%, and the PTA yield is as high as 93%.

[0031] Example 5: 12.0g of ammonium heptamolybdate tetrahydrate and 4.0g of 2-methylimidazole were dissolved in 120mL of deionized water, and 100mL of 1mol / L hydrochloric acid solution was added, and stirred at room temperature for 1.5h. Centrifuge and wash twice with deionized water and ethanol respectively to obtain a solid product. Then dry it in a 60℃ oven for 12h. The dried solid product was placed in a tube furnace, passed through Ar, and heated to 800℃ at a rate of 5℃ / min, maintained for 6h, and cooled to room temperature to obtain a molybdenum carbide catalyst. Take 0.3g of the prepared molybdenum carbide catalyst and 3.0g of polyethylene terephthalate (PET), place them in a high-pressure reactor, fill the reactor with 1.5MPa of hydrogen at room temperature, heat to 260℃, react for 12h, the conversion rate of PET reaches 100%, the selectivity of PTA in the solid product is higher than 99%, and the PTA yield is as high as 92%.

[0032] Example 6: 4.0g of ammonium heptamolybdate tetrahydrate and 1.3g of 2-methylimidazole were dissolved in 40mL of deionized water, and 30mL of hydrochloric acid solution with a concentration of 1mol / L was added, and stirred at room temperature for 0.5h. Centrifuge and wash twice with deionized water and ethanol respectively to obtain a solid product. Then dry it in a 60℃ oven for 12h. The dried solid product was placed in a tube furnace, and 5% H2 / Ar mixed gas was introduced. The temperature was raised to 700℃ at a rate of 3℃ / min, maintained for 6h, and cooled to room temperature to obtain a molybdenum carbide catalyst. Take 0.1g of the prepared molybdenum carbide catalyst and 1.0g of polyethylene terephthalate (PET), place them in a high-pressure reactor, fill the reactor with 0.1MPa of hydrogen at room temperature, heat to 280℃, react for 12h, the conversion rate of PET reaches 100%, the selectivity of PTA in the solid product is higher than 99%, and the PTA yield is as high as 90%.

[0033] Example 7: 5.75g of ammonium tungstate and 2.4g of 2-methylimidazole were dissolved in 40mL of deionized water, and 30mL of 1mol / L hydrochloric acid solution was added, and stirred at room temperature for 0.5h. Centrifuge and wash twice with deionized water and ethanol respectively to obtain a solid product. Then dry it in a 60℃ oven for 12h. The dried solid product was placed in a tube furnace, passed through Ar, and heated to 900℃ at a rate of 3℃ / min, and maintained for 1h to obtain a tungsten carbide catalyst. Take 0.1g of the prepared tungsten carbide catalyst and 1.0g of polyethylene terephthalate (PET), place them in a high-pressure reactor, fill the reactor with 1.5MPa of hydrogen at room temperature, heat to 260℃, react for 4h, the conversion rate of PET reaches 100%, the selectivity of PTA in the solid product is higher than 99%, and the PTA yield is as high as 89%.

[0034] Example 8: 5.75g of ammonium tungstate and 2.4g of 2-methylimidazole were dissolved in 40mL of deionized water, and 30mL of 1mol / L hydrochloric acid solution was added, and stirred at room temperature for 0.5h. Centrifuge and wash twice with deionized water and ethanol respectively to obtain a solid product. Then dry it in a 60℃ oven for 12h. The dried solid product was placed in a tube furnace, passed through Ar, and heated to 900℃ at a rate of 3℃ / min, and maintained for 1h to obtain a tungsten carbide catalyst. Take 0.1g of the prepared tungsten carbide catalyst and 1.0g of polybutylene terephthalate (PBT), place them in a high-pressure reactor, fill the reactor with 1.5MPa of hydrogen at room temperature, heat to 300℃, react for 6h, the conversion rate of PBT reaches 100%, the selectivity of PTA in the solid product is higher than 99%, and the PTA yield reaches 85%.

[0035] Example 9: 2.1g ammonium perrhenate and 1.4g 2-methylimidazole were dissolved in 40mL deionized water, and 20mL hydrochloric acid solution with a concentration of 1mol / L was added, and stirred at room temperature for 0.5h. Centrifuge and wash twice with deionized water and ethanol respectively to obtain a solid product. Then dry it in a 60℃ oven for 12h. The dried solid product was placed in a tube furnace, Ar was introduced, and the temperature was increased to 900℃ at a rate of 3℃ / min and maintained for 1h to obtain a carbonized rhenium catalyst. Take 0.1g of the prepared carbonized rhenium catalyst and 1.0g polyethylene terephthalate (PET), place them in a high-pressure reactor, fill the reactor with 1.5MPa of hydrogen at room temperature, heat to 280℃, react for 6h, the conversion rate of PET reaches 100%, the selectivity of PTA in the solid product is higher than 99%, and the PTA yield is as high as 88%.

[0036] Example 10: 2.1g ammonium perrhenate and 1.4g 2-methylimidazole were dissolved in 40mL deionized water, and 20mL of 1mol / L hydrochloric acid solution was added, and stirred at room temperature for 0.5h. Centrifuge and wash twice with deionized water and ethanol respectively to obtain a solid product. Then dry it in a 60℃ oven for 12h. The dried solid product was placed in a tube furnace, Ar was introduced, and the temperature was increased to 900℃ at a rate of 3℃ / min, and maintained for 1h to obtain a carbonized rhenium catalyst. Take 0.1g of the prepared carbonized rhenium catalyst and 1.0g of polybutylene terephthalate (PBT), place them in a high-pressure reactor, fill the reactor with 1.5MPa of hydrogen at room temperature, heat to 300℃, react for 6h, the conversion rate of PBT reaches 100%, the selectivity of PTA in the solid product is higher than 99%, and the PTA yield is as high as 87%.

[0037] Example 11: 2.0g of ferric acetylacetonate and 1.6g of 2-methylimidazole were dissolved in 40mL of deionized water, and 30mL of 1mol / L hydrochloric acid solution was added, and stirred at room temperature for 0.5h. Centrifuge and wash twice with deionized water and ethanol respectively to obtain a solid product. Then dry it in a 60℃ oven for 12h. The dried solid product was placed in a tube furnace, Ar was introduced, and the temperature was raised to 700℃ at a rate of 3℃ / min, and maintained for 1h to obtain an iron carbide catalyst. Take 0.1g of the prepared iron carbide catalyst and 1.0g of polyethylene terephthalate (PET), place them in a high-pressure reactor, fill the reactor with 1.5MPa of hydrogen at room temperature, heat to 280℃, react for 6h, the conversion rate of PET reaches 100%, the selectivity of PTA in the solid product is higher than 99%, and the PTA yield is as high as 86%.

[0038] Example 12: 2.81g ammonium metavanadate and 1.2g 2-methylimidazole were dissolved in 40mL deionized water, and 28mL hydrochloric acid solution with a concentration of 1mol / L was added, and stirred at room temperature for 0.5h. Centrifuge and wash twice with deionized water and ethanol respectively to obtain a solid product. Then dry it in a 60℃ oven for 12h. The dried solid product was placed in a tube furnace, Ar was introduced, and the temperature was raised to 900℃ at a rate of 3℃ / min and maintained for 1h to obtain a vanadium carbide catalyst. Take 0.1g of the prepared vanadium carbide catalyst and 1.0g polyethylene terephthalate (PET), place them in a high-pressure reactor, fill the reactor with 1.5MPa of hydrogen at room temperature, heat to 260℃, react for 4h, the conversion rate of PET reaches 100%, the selectivity of PTA in the solid product is higher than 99%, and the PTA yield is as high as 87%.

[0039] Example 13: 2.81g ammonium metavanadate and 1.2g 2-methylimidazole were dissolved in 40mL deionized water, and 28mL hydrochloric acid solution with a concentration of 1mol / L was added, and stirred at room temperature for 0.5h. Centrifuge and wash twice with deionized water and ethanol respectively to obtain a solid product. Then dry it in a 60℃ oven for 12h. The dried solid product was placed in a tube furnace, passed through Ar, and heated to 900℃ at a rate of 3℃ / min, and maintained for 1h to obtain a vanadium carbide catalyst. Take 0.1g of the prepared vanadium carbide catalyst and 1.0g polyethylene terephthalate (PBT), place them in a high-pressure reactor, fill the reactor with 1.5MPa of hydrogen at room temperature, heat to 300℃, react for 6h, the conversion rate of PET reaches 100%, the selectivity of PTA in the solid product is higher than 99%, and the PTA yield reaches 88%.

[0040] Example 14: On the basis of Example 1, 50 mL of 0.01 mol / L NaOH solution was added to the kettle after the reaction to separate the catalyst and the product. The recovered catalyst was washed with water and dried. The recovered catalyst was placed in the high-pressure reactor again, 1.0 g of polyethylene terephthalate (PET) was added, and 1.5 MPa of hydrogen was filled into the reactor at room temperature. The reaction was heated to 260°C and reacted for 4 hours. This step was repeated 10 times. The conversion rate of PET, the selectivity of PET in the solid product, and the yield of PET are shown in Table 1 below.

[0041] It can be seen from the results in Table 1 that the catalyst used in the present invention has good stability, and the reaction performance remains basically unchanged after 10 cycles of use.

[0042] Table 1

[0043] Cycle times PET conversion rate / % PET selectivity in solid products / % PET yield / % 1 100 99 91 2 100 99 91 3 99 99 91 4 99 99 91 5 99 99 91 6 98 98 90 7 98 98 90 8 98 99 90 9 98 99 90 10 98 99 90

[0044] Comparative Example 1: 4.0g of ammonium heptamolybdate tetrahydrate and 1.3g of 2-methylimidazole were dissolved in 40mL of deionized water, and 30mL of 1mol / L hydrochloric acid solution was added, and stirred at room temperature for 0.5h. Centrifuge and wash twice with deionized water and ethanol respectively to obtain a solid product. Then dry it in a 60℃ oven for 12h. The dried solid product was placed in a tube furnace, and a 20% O2 / Ar mixed gas was introduced. The temperature was raised to 700℃ at a rate of 3℃ / min, maintained for 1h, and cooled to room temperature. The catalyst obtained was MoO3. Take 0.1g of the prepared MoO3 catalyst and 1.0g of polyethylene terephthalate (PET), place them in a high-pressure reactor, fill the reactor with 1.5MPa of hydrogen at room temperature, heat to 260℃, and react for 4h. The conversion rate of PET is only 20%, and the yield of PTA is only 16%.

[0045] Comparative Example 2: 5.75g of ammonium tungstate and 2.4g of 2-methylimidazole were dissolved in 40mL of deionized water, and 30mL of 1mol / L hydrochloric acid solution was added, and stirred at room temperature for 0.5h. Centrifuge and wash twice with deionized water and ethanol respectively to obtain a solid product. Then dry it in a 60℃ oven for 12h. The dried solid product was placed in a tube furnace, and a 20% O2 / Ar mixed gas was introduced. The temperature was raised to 900℃ at a rate of 3℃ / min and maintained for 1h to obtain a WO3 catalyst. Take 0.1g of the prepared WO3 catalyst and 1.0g of polyethylene terephthalate (PET), place them in a high-pressure reactor, fill the reactor with 1.5MPa of hydrogen at room temperature, heat to 260℃, and react for 4h. The conversion rate of PET is only 16%, and the yield of PTA is only 11%.

[0046] Comparative Example 3: 2.81g ammonium metavanadate and 1.2g 2-methylimidazole were dissolved in 40mL deionized water, and 28mL hydrochloric acid solution with a concentration of 1mol / L was added, and stirred at room temperature for 0.5h. Centrifuge and wash twice with deionized water and ethanol respectively to obtain a solid product. Then dry it in a 60℃ oven for 12h. The dried solid product was placed in a tube furnace, 20% O2 / Ar mixed gas, heated to 900℃ at a rate of 3℃ / min, and maintained for 1h to obtain a V2O5 catalyst. Take 0.1g of the prepared V2O5 catalyst and 1.0g polyethylene terephthalate (PET), place them in a high-pressure reactor, fill the reactor with 1.5MPa of hydrogen at room temperature, heat to 260℃, react for 4h, the conversion rate of PET is only 12%, and the yield of PTA is only 8%.

[0047] Comparative Example 4: 2.1g ammonium perrhenate and 1.4g 2-methylimidazole were dissolved in 40mL deionized water, and 20mL of 1mol / L hydrochloric acid solution was added, and stirred at room temperature for 0.5h. Centrifuge and wash twice with deionized water and ethanol respectively to obtain a solid product. Then dry it in a 60℃ oven for 12h. The dried solid product was placed in a tube furnace, and a 20% O2 / Ar mixed gas was introduced, and the temperature was raised to 900℃ at a rate of 3℃ / min, and maintained for 1h to obtain a rhenium oxide catalyst. Take 0.1g of the prepared rhenium oxide catalyst and 1.0g of polyethylene terephthalate (PET), place them in a high-pressure reactor, fill the reactor with 1.5MPa of hydrogen at room temperature, heat to 280℃, and react for 6h. The conversion rate of PET is only 18%, and the yield of PTA is only 13%.

[0048] Comparative Example 5: 2.0g of ferric acetylacetonate and 1.6g of 2-methylimidazole were dissolved in 40mL of deionized water, and 30mL of 1mol / L hydrochloric acid solution was added, and stirred at room temperature for 0.5h. Centrifuge and wash twice with deionized water and ethanol respectively to obtain a solid product. Then dry it in a 60℃ oven for 12h. The dried solid product was placed in a tube furnace, and a 20% O2 / Ar mixed gas was introduced, and the temperature was raised to 700℃ at a rate of 3℃ / min, and maintained for 1h to obtain an iron oxide catalyst. Take 0.1g of the prepared iron oxide catalyst and 1.0g of polyethylene terephthalate (PET), place them in a high-pressure reactor, fill the reactor with 1.5MPa of hydrogen at room temperature, heat to 280℃, and react for 6h. The conversion rate of PET is only 8%, and the yield of PTA is only 5%.

Claims

1. A method for preparing terephthalic acid by hydrogenation degradation of waste polyester plastics, characterized in that: A high-pressure reactor is used to heat and stir waste polyester plastics in a H2 atmosphere under the action of a catalyst transition metal carbide, and terephthalic acid monomer is generated through solvent-free hydrogenation degradation; the transition metal carbide includes at least one of molybdenum carbide, tungsten carbide, vanadium carbide, iron carbide, and rhenium carbide; the polyester plastic is at least one of polyethylene terephthalate and polybutylene terephthalate.

2. The method for preparing terephthalic acid by hydrogenation degradation of waste polyester plastics as claimed in claim 1, characterized in that: The amount of the catalyst used accounts for 1% to 20% of the total mass of the waste polyester plastics.

3. The method for preparing terephthalic acid by hydrogenation degradation of waste polyester plastics as claimed in claim 1, characterized in that: The H2 pressure is 0.1-8 MPa, the reaction temperature is 180-300°C, and the reaction time is 0.1-24 h.

4. The method for preparing terephthalic acid by hydrogenation degradation of waste polyester plastics as claimed in claim 1, characterized in that: The transition metal carbide is selected from at least one of hexagonal molybdenum carbide, cubic molybdenum carbide, hexagonal tungsten carbide, cubic tungsten carbide, vanadium carbide, iron carbide, and rhenium carbide.

5. The method for preparing terephthalic acid by hydrogenation degradation of waste polyester plastics as claimed in claim 1, characterized in that: The preparation of the transition metal carbide is as follows: firstly, a soluble transition metal precursor and 2-methylimidazole are dissolved in water, then a hydrochloric acid solution is added and stirred, and the transition metal carbide is obtained by centrifugation, washing, drying and roasting.

6. The method for preparing terephthalic acid by hydrogenation degradation of waste polyester plastics as claimed in claim 5, characterized in that: The soluble transition metal precursor includes ammonium heptamolybdate tetrahydrate, sodium molybdate, ammonium tungstate, ammonium metatungstate, sodium tungstate, sodium metatungstate, ammonium vanadate, ammonium metavanadate, ammonium perrhenate, ferric chloride, ferric nitrate, ferric acetylacetonate, ferric sulfate, and ferric acetate.

7. The method for preparing terephthalic acid by hydrogenation degradation of waste polyester plastics as claimed in claim 5, characterized in that: The molar ratio of the soluble transition metal precursor to 2-methylimidazole is 1:1-10.

8. The method for preparing terephthalic acid by hydrogenation degradation of waste polyester plastics as claimed in claim 5, characterized in that: The molar ratio of the soluble transition metal precursor to hydrochloric acid is 1:0.1-4.

9. The method for preparing terephthalic acid by hydrogenation degradation of waste polyester plastics as claimed in claim 5, characterized in that: The calcination atmosphere is one of nitrogen, argon, 5% to 100% H2 hydrogen-argon or hydrogen-nitrogen mixed gas.

10. The method for preparing terephthalic acid by hydrogenation degradation of waste polyester plastics as claimed in claim 5, characterized in that: The calcination temperature is 600-900°C, and the calcination time is 1-24h.